2017
DOI: 10.1016/j.hrthm.2017.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous recordings of intrinsic cardiac nerve activity and skin sympathetic nerve activity from human patients during the postoperative period

Abstract: Background Intrinsic cardiac nerve activities (ICNA) and the skin nerve activities (SKNA) are both associated with cardiac arrhythmias in dogs. Objective To test the hypothesis that ICNA and SKNA correlate with postoperative cardiac arrhythmias in humans. Methods Eleven patients (60±13 years old; 4 female) were enrolled in this study. Electrical signals were simultaneously recorded from electrocardiogram (ECG) patch electrodes on the chest wall and from two temporary pacing wires placed during open heart s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…Atrial tachyarrhythmia episodes were invariably preceded by intrinsic cardiac nerve activity, thus support- and noninvasively record human skin sympathetic nerve activity, 19 has shown that increased skin and intrinsic cardiac nerve activities were associated with the development of paroxysmal atrial tachyarrhythmia episodes in humans. 14,15 These findings are consistent with those observed in canine models.…”
Section: Direct Recording Of the Ans And Atrial Tachyarrhythmiasupporting
confidence: 88%
See 1 more Smart Citation
“…Atrial tachyarrhythmia episodes were invariably preceded by intrinsic cardiac nerve activity, thus support- and noninvasively record human skin sympathetic nerve activity, 19 has shown that increased skin and intrinsic cardiac nerve activities were associated with the development of paroxysmal atrial tachyarrhythmia episodes in humans. 14,15 These findings are consistent with those observed in canine models.…”
Section: Direct Recording Of the Ans And Atrial Tachyarrhythmiasupporting
confidence: 88%
“…The role of ANS on cardiac arrhythmogenesis was evaluated by direct recording of autonomic nerve activity in ambulatory animals 12,13 and in humans. 14,15 There was circadian variation in the sympathetic outflow from the canine stellate ganglia. Simultaneous sympathovagal discharges often precede paroxysmal atrial tachycardia (AT) events.…”
Section: Direct Recording Of the Ans And Atrial Tachyarrhythmiamentioning
confidence: 99%
“…Basic and clinical studies have suggested that increased cardiac sympathetic nerve activity is thought to contribute to VAs [ 18 21 ]. It is well known that AMI releases various metabolites including ATP, protons, bradykinin, and histamine that stimulate cardiac sympathetic afferent nerve endings and lead to an activation of sympathetic nerve activity [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intrinsic cardiac nerve activities invariably preceded spontaneously occurring atrial tachyarrhythmias in a canine model of pacing-induced AF (75). In patients recovering from open heart surgery, these fat pad intrinsic cardiac nerve activities were associated with an increased burden of premature atrial complexes and might predict the development of post-operative AF (76).…”
Section: Atrial Myopathy and Autonomic Remodelingmentioning
confidence: 96%